2004
DOI: 10.1097/01.wcb.0000126236.54306.21
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Ischemic Brain by Vascular Endothelial Growth Factor is Critically Dependent on Proper Dosage and May Be Compromised by Angiogenesis

Abstract: Vascular endothelial growth factor (VEGF) is currently considered a potential pharmacologic agent for stroke therapy because of its strong neuroprotective and angiogenic capacities. Nonetheless, it is unclear how neuroprotection and angiogenesis by exogenous VEGF are related and whether they are concurrent events. In this study, the authors evaluated by stereology the effect of VEGF on neuronal and vascular volume densities of normal and ischemic brain cortices of adult male Sprague-Dawley rats. Ischemia was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 55 publications
4
86
0
Order By: Relevance
“…In cultured cerebellar granule neurons, hypoxia-induced tolerance also depends on VEGF/ VEGFR2 activation and Akt phosphorylation (Wick et al, 2002). However, once the dose of VEGF exceeds the limit, adverse effects of VEGF might surpass the neuroprotective effects and deteriorate neuronal survival and function in vivo and in vitro (Laudenbach et al, 2007;Manoonkitiwongsa et al, 2004;Yasuhara et al, 2005). Interestingly, we also found that 3 hours of hypoxia (8% O 2 ) induced a moderate upregulation (34%) of the VEGF protein in WT mice.…”
Section: Discussionsupporting
confidence: 54%
“…In cultured cerebellar granule neurons, hypoxia-induced tolerance also depends on VEGF/ VEGFR2 activation and Akt phosphorylation (Wick et al, 2002). However, once the dose of VEGF exceeds the limit, adverse effects of VEGF might surpass the neuroprotective effects and deteriorate neuronal survival and function in vivo and in vitro (Laudenbach et al, 2007;Manoonkitiwongsa et al, 2004;Yasuhara et al, 2005). Interestingly, we also found that 3 hours of hypoxia (8% O 2 ) induced a moderate upregulation (34%) of the VEGF protein in WT mice.…”
Section: Discussionsupporting
confidence: 54%
“…Neurons with pale nucleus and cytoplasm were considered viable neurons. Viable neurons with nucleolus were counted using a modified correction factor to adjust for partial profiles (Manoonkitiwongsa et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above data and on our findings, a novel therapeutic approach based on an early administration of both angiogenic factors leading to a limitation of the extent of neuronal death might be encouraged for the treatment of cerebral ischemia. However, it has been shown that neuroprotection and angiogenesis induced by VEGF monotherapy do not necessarily occur at the same dose of exogenous VEGF (Manoonkitiwongsa et al, 2004). Consequently, it would be necessarily, in the future, to investigate the role of endogenous VEGF and Ang-1 and to determine whether an optimal parenchymal concentration of both agents can safely stimulate both angiogenesis and neuroprotection in relation with an increase in functional outcome (Hori et al, 2004;Iizasa et al, 2002;Wang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%